Northern hemisphere cold air outbreaks are more likely to be severe during weak polar vortex conditions - Jinlong Huang (Nature Portfolio, 2021)
A weak stratospheric polar vortex in the Arctic leads to a disproportionally increased risk of severe cold air outbreaks over northern extratropical regions, compared to moderate outbreaks, suggest analyses of reanalysis data and climate model simulations.